Comparison of Selected Trading Strategies in The Forex Market - Zdeněk TOUŠEK; Miroslav DLOUHÝ; Tomáš RAIN (Communications of International Proceedings, 2023)
This paper examines the possibilities of combining basic technical indicators, when selected combinations of technical indicators are tested using MetaTrader 4 software using demo accounts. The reason for the processing was the growing interest in the foreign exchange market. For the survey, 4 technical indicators were selected: simple moving average; exponential moving average; stochastic, and relative force index. The objective of this paper was to answer two research questions: What business strategy (i.e., what combination of technical indicators) will lead to the highest profitability? And - which day of the week is favorable for forex trading? The paper found that the combination of the technical indicator, the exponential moving average together with the Stochastic oscillator leads to the greatest profitability and that Tuesday is the most profitable day for the execution of trades. The recommendation for increasing profitability in this trading strategy is to study supports and resistances, and then set stop loss (SL) and take profit (TP) based on them.
Keywords: Foreign exchange market; technical indicator; trading strategy; account.